Acesso da população ao diagnóstico e tratamento da esquistossomose em área endêmica no Município de Jequitinhonha, Minas Gerais - Dener Carlos dos Reis (2009)
This study examines the relationship between demographic, social, economic,geographic and health service patterns and the utilization of health-care by apopulation in diagnostic and treatment of schistosomiasis in City of São Pedro doJequitinhonha, State of Minas Gerais, Brazil. This study enrolled 1,228 subjects,including 935 residents of the central village, and 293 in rural area. Data collectionconsisted of a questionnaire with demographic, socioeconomic, cultural informationand access and utilization of health services related to diagnosis and treatment ofschistosomiasis in 2002 (active case findings), in addition to the period between 2002and 2006 (passive demand). Three stool test samples were taken from each subject,analyzed using the Kato-Katz method and subjects testing positive for S. mansoniwere treated with praziquantel. Focal groups were conducted with 30 residents andinterviews with health professionals to collect information regarding access to publichealth services and schistosomiasis control. Data analysis involved the following:descriptive analysis according to residence, univariate and multivariate logisticregression with a Generalized Estimation Equation (GEE). The interviews and focusgroups were analyzed according to the analysis of Bardin. Results pointed to aninequity to access and the utilization of health care by the target population in thediagnostic and treatment of schistosomiasis. The main barriers associated with lowutilization rate at the individual level were poor economic conditions, lack ofknowledge by subjects regarding schistosomiasis and a high rate of homemedication consumption. At the health services level, the main barriers were lack ofroutine stool-sample collection testing at local health services, the centralization ofpraziquantel in Jequitinhonha Municipality and the lack of health education programs.Access to the ongoing cases by the health service, in 2002, differed between centralvillage and rural residents, and this strategy for schistosomiasis control does notoccur as directed according to protocol procedures by the Brazilian Ministry ofHealth. The large distances between the rural residences, in addition to thegeographical barrier caused by the Jequitinhonha River, a lack of publictransportation, are such factors that may have contributed to low rate of health-careutilization for diagnostic and treatment of schistosomiasis. These barriers associatedwith lack of sanitation conditions have contributed to high disease prevalence andlack of control of schistosomiasis in this study area. Our results showed majordifferences in perception and knowledge of schistosomiasis control between usersand health services providers. Results suggest the need to accelerate thedissemination of schistosomiasis control program at primary health services in orderto make them more accessible to the at-risk population in the Sao Pedro District. Thismust include a health education program that will focus on health promotion andactive participation of the community.